Anglophone And Civilian: Two Legal Cultures For The Global Age - Joseph P. Garske (European Scientific Journal, ESJ, 2016)
This paper compares two methods of law, Civilian and Anglophone. It discusses how any legal culture must have two aspects, the adjudicative and the educative. It explores the origin of both legal traditions in the medieval world, and how thy both were transformed by the great technological developments of the fifteenth century. It examines how both traditions adapted themselves to the new circumstance of modernity. Finally, it shows how the rise of a new style university and school in the nineteenth century completed a modern type of legal culture. The paper concludes by reviewing the implications of these past events, in assessing the effect of either law, as a basis of global order in the future.